2016
DOI: 10.1213/ane.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Morphologic Obstructive Sleep Apnea Prediction Score

Abstract: DES-OSA is a simple score for detecting OSA patients. Its originality relies on its morphologic nature. Derived from a European population, it may prove useful in a preoperative setting, but it has still to be compared with other screening tools in a general surgical population and in other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…We recently reported the results of a study (EudraCT: 2006-006558-92) that outlined the development of the DES-OSA score (the DES part of the acronym being derived from the initials of the investigators involved in its development) in 139 patients. 4 The Figure shows the relation between the ODI and the AHI from that study. Clearly, some, but not all, patients with severe OSA (AHI [ 30) experienced nocturnal hypoxia.…”
mentioning
confidence: 92%
“…We recently reported the results of a study (EudraCT: 2006-006558-92) that outlined the development of the DES-OSA score (the DES part of the acronym being derived from the initials of the investigators involved in its development) in 139 patients. 4 The Figure shows the relation between the ODI and the AHI from that study. Clearly, some, but not all, patients with severe OSA (AHI [ 30) experienced nocturnal hypoxia.…”
mentioning
confidence: 92%
“…For example, Marrone et al demonstrated in a cohort of patients (from the European Sleep Apnea Database) that the combination of severe OSA and nocturnal hypoxemia might be an important risk factor for kidney dysfunction. 5 We have read with great interest the letter of Chung et al 6 wherein they highlighted the deleterious influence of nocturnal hypoxemia on the postoperative complication rate. Their letter confirmed to us that future studies must be specifically designed to recognize the possible influence of the nocturnal hypoxemia/severe OSA combination vs nocturnal hypoxemia alone or severe OSA alone.…”
Section: To the Editormentioning
confidence: 99%
“…In future studies, special attention should also be directed to identifying patients with thisnocturnal hypoxemia/severe OSA combination in a surgical population (e.g., using screening tools such as STOP-Bang and DES-OSA). 6 …”
Section: To the Editormentioning
confidence: 99%
“…Besides the effort to reduce the number of undiagnosed cases of OSA, it is of general interest among surgeons and anesthesiologists to estimate the postoperative outcome ofpatients with OSA [2]. Therefore, scientists developed a clinical screening in a sleep center, in a population with a high incidence of OSA.…”
Section: Predictors Of Obstructive Sleep Apnea Anthropometric Measurementioning
confidence: 99%
“…Therefore, scientists developed a clinical screening in a sleep center, in a population with a high incidence of OSA. The test ought to define the severity of OSA and contains Mallampati Index, the distance between thyroid and chin (cm), neck circumference (cm), BMI (kg/m 2 ), and gender [2]. Despite all these approaches there is still an intense debate on the significance and hierarchy of all possible predictors of OSA.…”
mentioning
confidence: 99%